"I know my body better than you:" patient focus groups to inform a decision aid on oral corticosteroid use during pregnancy. Issue 4 (22nd December 2020) - Palmsten, Kristin; Bredesen, Dani; JaKa, Meghan M.; Kumar, Pritika C.; Ziegenfuss, Jeanette Y.; Kharbanda, Elyse O.
Abstract: Purpose: There is unmet need for decision support regarding medication use during pregnancy. We aimed to inform the development of a decision aid on oral corticosteroid (OCS) use during pregnancy through focus groups. Methods: We invited patients from one health system who had a recent live birth and a condition for which OCSs may be prescribed (ie, asthma or other autoimmune disease) to participate in focus groups. We conducted conventional qualitative content analysis of verbatim transcripts of the focus groups using inductive coding. Results: There were 30 participants across five focus groups from May to June 2019. Women endorsed the need for patient‐provider discussions about OCS use during pregnancy in which the provider shares risks and benefits and the patient makes her decision. Furthermore, women generally expressed support for patient‐centered handouts about OCS use during pregnancy that the provider discusses with the patient. When considering whether to take OCSs in pregnancy, women had concerns about: the medication's impact on their baby (eg, miscarriage, birth defects, long‐term effects), themselves (eg, effects on mood, sleep, weight gain), pregnancy complications (eg, preterm birth, increased blood pressure), and lactation. Women wanted information on OCSs (eg, indications, length of treatment, and cost), alternative treatments, and risks of not taking OCSs. Conclusions: We established patient need for a decision aid on OCS use during pregnancy that providers can discuss with patients. To address patient concerns, the aid should at a minimum describe the medication's impact on baby, including long‐term effects, maternal health, pregnancy complications, and lactation.